IL-18 receptor axis in allergic conjunctivitis: a multi-omics study - Yuan, Liyun; Su, Wangming; Li, Liangpin; Xiang, Yang; Xu, Zijiao; Wang, Yuchuan; Hua, Xia; Yuan, Xiaoyong (Frontiers in Immunology, 2025)
PurposeThe pathophysiology of allergic conjunctivitis (AC) is not fully explained by the traditional Th2-centric model. This study aimed to identify AC-associated candidate genes and delineate immune pathways, with a focus on cell-type–specific mechanisms that could contribute to disease heterogeneity.MethodsWe employed an integrative multi-omics strategy, using three genomic analyses (FUSION, MAGMA, UTMOST) on human GWAS data to identify AC-associated candidate genes. These candidates were then investigated using single-cell RNA sequencing data from a mouse model of AC to map immune cell communication and signaling dynamics. Key pathways were validated in an independent ovalbumin-induced AC mouse model using clinical scoring, qRT-PCR and Western blot analysis.ResultsThis approach identified nine high-confidence AC-associated candidate genes, including key components of the IL-1 and Toll-like receptor families. In the AC mouse model, the IL-18 receptor components Il18r1 and Il18rap were selectively upregulated in NK and T cells from allergic versus control mice and correlated positively with interferon-γ (Ifng) expression. Cell–cell communication and pseudotime analyses indicated an allergic-state network characterized by enhanced NK cell–linked IFN-γ signaling to antigen-presenting cells and dynamic changes in NF-κB and JAK–STAT pathway activity. In the OVA-induced model, conjunctival IL-18, IL-18R1, IL-18RAP and phosphorylated NF-κB p65 were increased in AC versus controls and showed a stepwise rise across mild, moderate and severe clinical groups.ConclusionsAcross human genetics, single-cell transcriptomics and in vivo validation, an IL-18 receptor/IFN-γ axis in NK and T cells emerges as a reproducible module associated with AC and its severity. These findings extend the immunopathological framework of AC beyond a purely Th2-driven process and nominate IL-18R-linked signaling as a candidate pathway for future mechanistic and therapeutic studies.